An Evaluation of Early Childhood Education at Provincial Level: Policies, Practices, Issues, and Challenges in Baluchistan (Journal of Social Sciences Review, 2023)
The topic of this literature review article is "ECCE Policy and Practice in Baluchistan". The article aims to critically analyze the existing policy framework and ECCE practices in Baluchistan and identify improvement opportunities. It provides recommendations and strategies for increasing parental and community involvement in ECCE programs. Overall, the article aims to provide insights and recommendations for improving the quality of ECCE services in Baluchistan based on a thorough review and analysis of existing literature. It involves conducting a comprehensive search for relevant literature on ECCE policy and practice in Baluchistan, evaluating the quality and credibility of the sources, synthesizing the information, and identifying common themes, issues, and challenges related to the topic. The review and analysis of existing literature also involve analyzing the strengths and weaknesses of the existing policy framework and ECCE practices in Baluchistan, evaluating the impact of ECCE services on child development and future education, and providing recommendations and strategies for improving the quality of ECCE services in Baluchistan based on the findings from the literature review. Overall, the review and analysis of existing literature is a crucial aspect of this article as it provides a comprehensive understanding of ECCE policy and practice in Baluchistan and informs recommendations for improvement.
Keywords: Education; Early Education; ECCE; Challenges